2018
DOI: 10.1007/s11540-017-9350-3
|View full text |Cite
|
Sign up to set email alerts
|

Carrot Pathogen ‘Candidatus Liberibacter solanacearum’ Haplotype C Detected in Symptomless Potato Plants in Finland

Abstract: Candidatus Liberibacter solanacearum' (CLso) haplotype C, a bacterial pathogen transmitted by the carrot psyllid Trioza apicalis, causes yield losses in carrot production. Due to concerns that this pathogen might also threaten potato (Solanum tuberosum) production, the occurrence of CLso in cultivated and volunteer potatoes in Tavastia Proper and Satakunta regions of Finland was studied. Volunteer potato plants were found in 13 of the 27 inspected carrot fields. Of the 148 potato samples tested by PCR, eight v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…In addition, previous studies using sampling methods at the level of the crop canopy have shown that the main psyllid species present in carrot fields is B. trigonica, followed by B. nigricornis in low proportions [27,29]. Several previous studies on bacterial transmission by psyllid species in nonhost plant species found that: T. apicalis (a vector of CaLsol in Apiaceae species in northern Europe) does not transmit the bacterium from carrot to potato [16], B. trigonica (a vector of CaLsol in Apiaceae species in southern Europe and North Africa) was able to transmit CaLsol at a low rate from carrot to potato or tomato [45,54], and the transmission of CaLsol to carrots by B. cockerelli (vector of CaLsol in Solanaceae species) was possible at a low rate and induced disease symptoms [62]. On the one hand, B. tremblayi could acquire CaLsol from infected carrot plants, but it could not transmit the bacterium to carrot plants, which might be because the bacterium was not able to complete circulation in the body of the psyllid to be ultimately inoculated from the salivary glands [45].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, previous studies using sampling methods at the level of the crop canopy have shown that the main psyllid species present in carrot fields is B. trigonica, followed by B. nigricornis in low proportions [27,29]. Several previous studies on bacterial transmission by psyllid species in nonhost plant species found that: T. apicalis (a vector of CaLsol in Apiaceae species in northern Europe) does not transmit the bacterium from carrot to potato [16], B. trigonica (a vector of CaLsol in Apiaceae species in southern Europe and North Africa) was able to transmit CaLsol at a low rate from carrot to potato or tomato [45,54], and the transmission of CaLsol to carrots by B. cockerelli (vector of CaLsol in Solanaceae species) was possible at a low rate and induced disease symptoms [62]. On the one hand, B. tremblayi could acquire CaLsol from infected carrot plants, but it could not transmit the bacterium to carrot plants, which might be because the bacterium was not able to complete circulation in the body of the psyllid to be ultimately inoculated from the salivary glands [45].…”
Section: Discussionmentioning
confidence: 99%
“…That is why, as authors, we believe that the CaLsol infection in citrus plants was not systemic. In a previous paper by Haapalainen et al [16], the transmission of CaLsol haplotype C through dodder and grafting onto potato was performed, but the transmission rate was very low; the bacteria did not colonize neither the root tissues nor the tubers. The reasons remain unknown, but they could be related to the specificity of the CaLsol haplotype, which could have different interactions with alternative hosts but also the cultivar assayed could be more resistant than others used in America [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations